2014
DOI: 10.1007/s10822-014-9804-5
|View full text |Cite|
|
Sign up to set email alerts
|

A desirability function-based scoring scheme for selecting fragment-like class A aminergic GPCR ligands

Abstract: A physicochemical property-based desirability scoring scheme for fragment-based drug discovery was developed for class A aminergic GPCR targeted fragment libraries.Physichochemical property distributions of known aminergic GPCR-active fragments from the ChEMBL database were examined and used for a desirability function-based score. Propertydistributions such as logD (at pH = 7.4), PSA, pK a (strongest basic center), number of nitrogen atoms, number of oxygen atoms, and the number of rotatable bonds were combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…In our recent study 1 we developed a ligand-based desirability function to enrich libraries with compounds potentially active on aminergic G-protein coupled receptor (GPCR) targets. The fragment aminergic GPCR score (FrAGS) provides computationally inexpensive, physicochemical property-based filtering of extensive public or proprietary databases consisting of hundreds of thousands to millions of entries.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our recent study 1 we developed a ligand-based desirability function to enrich libraries with compounds potentially active on aminergic G-protein coupled receptor (GPCR) targets. The fragment aminergic GPCR score (FrAGS) provides computationally inexpensive, physicochemical property-based filtering of extensive public or proprietary databases consisting of hundreds of thousands to millions of entries.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fragment screening provides diverse chemotypes and significant operational freedom for the further optimization of promising hits. Inspired by these advantages in a recent study we developed a strategy for aminergic focused fragment libraries using a sequential filtering methodology applying ligand- and structure-based scoring functions [ 4 , 5 ]. The prospective validation was performed on our in-house library of 1183 fragments.…”
Section: Resultsmentioning
confidence: 99%
“…Although these compounds have a common tryptamine derived motif, a ChEMBL-analysis [ 3 ] revealed that no representatives have been ever tested against serotonergic targets. Developing ligand-(FrAGs) [ 4 ] and structure-based (FrACS) [ 5 ] methods for the identification of aminergic receptor ligands we identified 6 as a micromolar 5-hydroxytryptamine receptor 6 (5-HT 6 R) ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, modification of the scoring function should take into account structural differences among ligands. Recent pose scoring based on ligand physicochemical properties [52] may be the way to explore these possibilities.…”
Section: Discussionmentioning
confidence: 99%